Effects of Supply Chain Strategy on Company Performance : The Moderating Role of Competitive Advantage - Niken Sulistyowati; Wahyu Dwi Purnomo (International Journal of Supply Chain Management, 2020)
The research aims to determine and analyze the effects of Supply Chain strategy on company performance through competitive advantage. Based on the description, this research was causal associative, using primary data with 343 respondents. Data collection technique used questionnaire, the instrument measurement scale was semantic differential. Data analysis used Structural Equation Model (SEM), which was operated using AMOS program. The results show that 1) supply chain strategy has a positive effect on competitive advantage, 2) competitive advantage has a positive effect on company performance, 3) supply chain strategy has no direct effect on company performance, but it has an indirect effect on company performance through competitive advantage. The implication of an effective company policy is to give priority to agile strategies, immediately respond to changes in innovative product designs, in accordance with the wishes of customers.